Social Media Marketing, Content Marketing, Email Marketing, and SEO Impact on Employee Engagement and Financial Performance in Indonesian Start-up Companies - Abdul Rahman Arie Wicaksono; Titin Endrawati (Westscience Press, 2025)
The present research work has focused on how the integration of techniques like Social Media Marketing, Content Marketing, Email Marketing, and SEO impacts the employee engagement and financial performance in Indonesian start-up companies. A quantitative approach was utilized, with 113 participants in the sample. The measurement of the Likert scale was within the range of 1 to 5. The data analysis was conducted using the Structural Equation Modeling with Partial Least Squares software. Results indicated a positive significant effect of Social Media Marketing, Content Marketing, and Email Marketing on Employee Engagement. Further, the study revealed that Employee Engagement has a significant influence on Financial Performance. The results imply that digital marketing strategies are effective tools of improving employee engagement, which contributes to improved financial performance in a start-up company. This study provides useful lessons that could be used by companies in pursuit of effective marketing both internally and externally to ensure better financial outcomes.